Hedging Foreign Exchange Exposures: Independent vs Integrative Approaches - Kwok, Chuck C. Y. (Journal of International Business Studies, 1987)
Many financial managers think that foreign exchange hedging decisions are mainly a choice between to hedge or not to hedge. Nevertheless, previous researchers applied Ederington's portfolio approach and found that even for risk minimization, a complete hedge does not lead to the lowest risk. Instead, there exists an optimal hedging ratio which yields the lowest variance. However, the discussions of these former studies were concentrated on a single foreign currency cash flow. In the real world, financial managers are more likely to expect multiple cash flows arriving at different times even for the same foreign currency. This paper therefore discusses whether financial managers should hedge these cash flows independently or combine them under one integrative hedging scheme. It is shown that, while the independent approach does not lead to the lowest risk, its hedging effectiveness is close to that of the integrative approach. Given the time and resource constraints of financial managers, the simpler independent approach appears to be a better choice.